Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Uncovering the hidden world of riverbed sediments: The role of sediment heterogeneity and cross-bar channel fills in the hydrogeochemical dynamics of the hyporheic zone - Jeffery T. McGarr; Pei Li; Robert G. Ford; Teagan Kleman; Colton Fields; Julie Hobbs; Lydia Lupton; Emma Poston; Thomas Marsh; Leah Trutschel; Ken M. Fritz; Annette Rowe; et al. (Journal of Hydrology, 2024)

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

Variability in surface CO2 flux: Implication for monitoring surface emission from geothermal fields - Tsung-Han Jimmy Yang; Isabelle Chambefort; Michael Rowe; Agnes Mazot; Anya Seward; Cynthia Werner; Tobias Fischer; Jun Seastres; Farrell Siega; Nick Macdonald; Thomas Brakenrig; Lauren Coup; et al. (Geothermics, 2024)

Exploring the internal textures and physical properties of digitate sinter in hot springs: Implications for remote sampling on Mars - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Ang; Steve Matthews; Steven W. Ruff; Ashok Meghwal; Ludmila Adam; Niamh Galligan; Thomas Loho (Planetary and Space Science, 2023)

Land degradation neutrality: Testing the indicator in a temperate agricultural landscape - Amy Thomas; Laura Bentley; Chris Feeney; Stephen Lofts; Ciaran Robb; Ed C Rowe; Amanda Thomson; Eleanor Warren-Thomas; Bridget Emmett (Journal of Environmental Management, 2023)

Guidelines for the selection of corrosion resistant alloys for CCS and CCUS injection wells - Bruce Craig; Adam Rowe; Michael Warmack; Thomas E. Doll; Catherine Stevens; Kevin C. Connors (International Journal of Greenhouse Gas Control, 2023)

Book review - Jenna E. Bayne; Thomas Passler; Joan D. Rowe (Small Ruminant Research, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Lake morphometry determines Dreissena invasion dynamics - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Knut Mehler; Mark D. Rowe; Ashley K. Elgin; Thomas F. Nalepa (Biological Invasions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

A Holocene record of savanna vegetation dynamics in southern lowland Papua New Guinea - Cassandra Rowe; Bruno David; Jerome Mialanes; Sean Ulm; Fiona Petchey; Samantha Aird; Ian J. McNiven; Matthew Leavesley; Thomas Richards (Vegetation History and Archaeobotany, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Liver and muscle glycogen oxidation and performance with dose variation of glucose–fructose ingestion during prolonged (3 h) exercise - Andy J. King; John P. O’Hara; Nicola C. Arjomandkhah; Josh Rowe; Douglas J. Morrison; Thomas Preston; Roderick F. G. J. King (European Journal of Applied Physiology, 2019)

Isolation by marine barriers and climate explain areas of endemism in an island rodent - Thomas C. Giarla; Sean P. Maher; Anang S. Achmadi; Meagan K. Moore; Mark T. Swanson; Kevin C. Rowe; Jacob A. Esselstyn (Journal of Biogeography, 2018)
Aim The Indonesian island of Sulawesi is home to thousands of endemic terrestrial animal species. Phylogeographical studies of some of these taxa revealed concordant distribution patterns (areas of endemism; AoEs), suggestive of a shared evolutionary or ecological mechanism driving divergence among various terrestrial taxa. Generally, AoEs have been attributed to Pleistocene marine incursions, geological fault zones and Sulawesi's history as an archipelago. We test, for the first time, the hypothesis that population divergences are associated with unsuitable climate spaces at the boundaries between these areas. Location Sulawesi, Indonesia. Taxon Maxomys musschenbroekii , a common murid rodent endemic to Sulawesi. Methods We sequenced a mitochondrial gene, four nuclear protein‐coding genes and hundreds of ultraconserved elements from individuals sampled across the island, which we used to build intraspecific phylogenies and identify population structure. To test climate‐related hypotheses, we used multiple regression to assess the extent to which genetic distances, over‐land geographical distances, environmental distances (derived from ecological niche model resistance surfaces) and areas of endemism are correlated. Results In all three genetic datasets, we inferred phylogeographical structure that is geographically concordant with previously defined AoEs. Ecological niche models showed a similar geography of suitability across the island since the Last Glacial Maximum, with varying levels of unsuitable climate space between AoEs. Genetic distances were more strongly correlated with environmental distances than geographical distances and interspecific divergences arose just in the past 1.5 Myr. Main Conclusions Population divergences within M. musschenbroekii are consistent with AoE definitions from other taxa. Stable areas of unsuitable habitat near AoE boundaries probably supplemented marine incursions in generating population structure within M. musschenbroekii and other co‐distributed species.

Collision activity during training increases total energy expenditure measured via doubly labelled water - Nessan Costello; Kevin Deighton; Thomas Preston; Jamie Matu; Joshua Rowe; Thomas Sawczuk; Matt Halkier; Dale B. Read; Daniel Weaving; Ben Jones (European Journal of Applied Physiology, 2018)

Temporal shifts in the saltmarsh–Nelson’s sparrow hybrid zone revealed by replicated demographic and genetic surveys - Jennifer Walsh; W. Gregory Shriver; Maureen D. Correll; Brian J. Olsen; Chris S. Elphick; Thomas P. Hodgman; Rebecca J. Rowe; Kathleen M. O’Brien; Adrienme I. Kovach (Conservation Genetics, 2017)

Local endemism and within‐island diversification of shrews illustrate the importance of speciation in building Sundaland mammal diversity - Terrence C. Demos; Anang S. Achmadi; Thomas C. Giarla; Heru Handika; Maharadatunkamsi; Kevin C. Rowe; Jacob A. Esselstyn (Molecular Ecology, 2016)
Island systems are important models for evolutionary biology because they provide convenient, discrete biogeographic units of study. Continental islands with a history of intermittent dry land connections confound the discrete definitions of islands and have led zoologists to predict (i) little differentiation of terrestrial organisms among continental shelf islands and (ii) extinction, rather than speciation, to be the main cause of differences in community composition among islands. However, few continental island systems have been subjected to well‐sampled phylogeographic studies, leaving these biogeographic assumptions of connectivity largely untested. We analysed nine unlinked loci from shrews of the genus Crocidura from seven mountains and two lowland localities on the Sundaic continental shelf islands of Sumatra and Java. Coalescent species delimitation strongly supported all currently recognized Crocidura species from Sumatra (six species) and Java (five species), as well as one undescribed species endemic to each island. We find that nearly all species of Crocidura in the region are endemic to a single island and several of these have their closest relative(s) on the same island. Intra‐island genetic divergence among allopatric, conspecific populations is often substantial, perhaps indicating species‐level diversity remains underestimated. One recent (Pleistocene) speciation event generated two morphologically distinct, syntopic species on Java, further highlighting the prevalence of within‐island diversification. Our results suggest that both between‐ and within‐island speciation processes generated local endemism in Sundaland, supplementing the traditional view that the region's fauna is relictual and primarily governed by extinction.

Use of free-standing filters in an asthma intervention study - Stuart Batterman; Liuliu Du; Edith Parker; Thomas Robins; Toby Lewis; Bhramar Mukherjee; Erminia Ramirez; Zachary Rowe; Wilma Brakefield-Caldwell (Air Quality, Atmosphere & Health, 2013)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Do surf zones in New Jersey provide “nursery” habitat for southern fishes? - Kenneth W. Able; Mark J. Wuenschel; Thomas M. Grothues; James M. Vasslides; Peter M. Rowe (Environmental Biology of Fishes, 2013)

High-resolution radiocarbon dating of marine materials in archaeological contexts: radiocarbon marine reservoir variability between Anadara, Gafrarium, Batissa, Polymesoda spp. and Echinoidea at Caution Bay, Southern Coastal Papua New Guinea - Fiona Petchey; Sean Ulm; Bruno David; Ian J. McNiven; Brit Asmussen; Helene Tomkins; Nic Dolby; Ken Aplin; Thomas Richards; Cassandra Rowe; Matthew Leavesley; Herman Mandui (Archaeological and Anthropological Sciences, 2013)

Near-Surface Larval and Juvenile Fish in Coastal Habitats: Comparisons Between the Inner Shelf and an Estuary in the New York Bight During Summer and Fall - Kenneth W. Able; Thomas M. Grothues; Peter M. Rowe; Mark J. Wuenschel; James M. Vasslides (Estuaries and Coasts, 2011)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

Organization of the Olfactory and Respiratory Skeleton in the Nose of the Gray Short-Tailed Opossum Monodelphis domestica - Timothy B. Rowe; Thomas P. Eiting; Thomas E. Macrini; Richard A. Ketcham (Journal of Mammalian Evolution, 2005)

Development and Growth Form of the Neotropical Liana Croton nuntians: The Effect of Light and Mode of Attachment on the Biomechanics of the Stem - Friederike Gallenmller; Nick Rowe; Thomas Speck (Journal of Plant Growth Regulation, 2004)

Diversity of Mechanical Architectures in Climbing Plants: An Evolutionary Perspective - Nick Rowe; Sandrine Isnard; Thomas Speck (Journal of Plant Growth Regulation, 2004)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

DQAsomes: A Novel Potential Drug and Gene Delivery System Made from Dequalinium™ - Volkmar Weissig; Jürgen Lasch; Gregory Erdos; Helmut W. Meyer; Thomas C. Rowe; Jeffrey Hughes (Pharmaceutical Research, 1998)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)